The Meaning of Stigma About Illegal Drug Use and Its Contribution to Public Policymaking in Colombia (2024)
ABSTRACT: The objective of this study is to understand the meaning of the stigma about illegal drug consumption and its contribution to public policymaking in Colombia from the perspective of experts on this topic. Research was carried out based on the methodological perspective of the grounded theory. Twenty participants with extensive experience in the design of regulations, plans, or programs about demand reduction in Colombia were interviewed, using tools such as in-depth interviews and analytical memos. The analysis was performed by means of open, axial, and selective coding techniques and the development of a conditional/consequential matrix. The fndings are presented according to the structure of the pattern matrix to show the social process found and include (a) the phenomenon, the fear of being stigmatized as a promoter of more liberal public policies; (b) the context, the Colombia’s history and the policymaking to reduce drug consumption; (c) the conditions, control of governance by infuential groups in power; and (d) the strategies to address it, prioritize less sensitive issues, and the consequences, formulation of repressive public policies with the impact on the rights of people who use drugs. From the perspective of the interviewees, the fear of being stigmatized as promoters of more liberal public policies and contrary to the expectations of the social and power classes leads the rulers to have a low-profle discourse on this subject so as not to assume the costs politicians that this fact would imply.